PRINCIPLES OF GNSS: PRINCIPLES OF GNSS - Ivanov, Sabin (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The most direct method for obtaining spatial information in digital form is the use of data from Polish geodetic measurements obtained from the global satellite location identification system. Global location systems GNSS belong to non-photographic recording systems of the group of remote methods for Earth measurements. The most popular system is GPS (Global Positioning System), designed and controlled by the US Department of Defense.